Analisis Kesulitan Siswa-Siswi Sekolah Menengah Pertama terhadap Pembelajaran Matematika - ‘Aisyah Naurah Salsabila; Arsya Putri Khairunnisa; Ilma Nur Safira; Rinjania Rinjania (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Learning difficulties refer to a group of difficulties that are manifested in the form of real difficulties in the proficiency and use of abilities in problem solving, reasoning, communication, and skills in the field of mathematics. The purpose of this study was to analyse students' learning difficulties in learning mathematics with the research subjects being grade 7 students of State Junior High School 51 Bandung. The instrument used was a questionnaire. The results showed that students' learning difficulties in mathematics subjects in terms of the percentage of internal factors were 88% in the high category with details: not liking mathematics, external factors were 91% in the high category with details: learning that was not fun and difficult to understand, teacher factors 12% in the low category, environmental factors 71% in the high category. So there are only a small number of students who like mathematics.